2012
DOI: 10.1038/mi.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1 expression in the conjunctiva is involved in immune cell trafficking during toxic ocular surface inflammation

Abstract: Inappropriate expression of the chemokine CX3CL1 is reportedly known to act on inflammatory conditions in extraocular immune diseases. We studied the expression and effects of CX3CL1 in human patients, cultured human conjunctival cells, and transgenic mice exposed to benzalkonium chloride (BAC), a commonly used preservative in ophthalmic medications despite its proinflammatory properties, to determine whether CX3CL1 is involved in conjunctival inflammation. We report that CX3CL1 expression is increased in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…These results are consistent with the in vivo and pathological findings, including stronger inflammatory responses in the C57BL/6 mice (vs. BALB/c mice) and during the first week (vs. second week). Denoyer et al have documented that the expression of CX3CL1, a member of the CX3C-chemokine subfamily that binds to its specific receptor CX3CR1 and induces the migration and activation of CX3CR1-bearing cells such as T cells, natural killers (NKs), monocytes, monocyte-derived macrophages and dendritic cells, was increased in the conjunctiva of patients and mice treated with BAC-containing eye drops [9]. Our current results, as well as recent reports by Kim, provide evidence of the high expression of chemokines in corneas treated with BAC [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with the in vivo and pathological findings, including stronger inflammatory responses in the C57BL/6 mice (vs. BALB/c mice) and during the first week (vs. second week). Denoyer et al have documented that the expression of CX3CL1, a member of the CX3C-chemokine subfamily that binds to its specific receptor CX3CR1 and induces the migration and activation of CX3CR1-bearing cells such as T cells, natural killers (NKs), monocytes, monocyte-derived macrophages and dendritic cells, was increased in the conjunctiva of patients and mice treated with BAC-containing eye drops [9]. Our current results, as well as recent reports by Kim, provide evidence of the high expression of chemokines in corneas treated with BAC [24].…”
Section: Discussionmentioning
confidence: 99%
“…Removal of BAC from timolol can improve the function of the corneal epithelial barrier and reduce patient complaints [7]. Additionally, significant increases in the conjunctival expression of inflammatory factors, e.g., C-X3-C motif chemokine 1 (CX3CL1), interleukins, C-C chemokine receptor 4 (CCR4) and C-C chemokine receptor 5 (CCR5), have been observed in patients treated with BAC-preserved eye drops over long periods of time [8,9]. These clinical studies have revealed an increasing incidence of adverse events with BAC and have demonstrated that the withdrawal of preservatives reduces these effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Celles-ci pourraient participer à la trabéculopathie glaucomateuse, en modulant l'inflammation locale et le recrutement des cellules immunes, la peroxydation lipidique et la production de ROS [64], ainsi que certains processus de fibrose tissulaire [52]. Certaines cytokines singulières, les chimiokines, impliquées dans l'homéostasie et l'inflammation du microenvironnement tissulaire, ont été identifiées au sein de la conjonctive [65,66], de la cornée [67,68], mais aussi du trabéculum [69,70] (Fig. 2).…”
Section: La Cellule Trabéculaire : Une Cible Thérapeutique De Choix ?unclassified
“…Apoptosis may be due to the release of cytochrome c in the cytoplasm from mitochondria and the activation of caspase-3 or to the translocation of factor AIF from mitochondria to the nucleus (Clouzeau et al 2012). Moreover, BAK promotes the activation of an inflammatory environment by synthesis and secretion of eicosanoids and many inflammatory mediators, such as interleukin (IL)-la, tumour necrosis factor-a, IL-8, IL-10, IL-12 (Epstein et al 2009;Denoyer et al 2012). Another study showed that BAK is associated with overexpression of inflammation-or apoptosis-related molecules such as HLA-DR, intercellular adhesion molecule 1 (ICAM-1), Fas antigen and the apoptotic marker Apo (Baudouin et al 2008).…”
Section: Introductionmentioning
confidence: 99%